Development of Interactive E-Module Based on Human Digestive System Material Inquiry on Theme 3 About Healthy Foods for Fifth Grade Elementary School - Ni Made Adelia Sari; Ida Bagus Surya Manuaba (Indonesian Journal Of Educational Research and Review, 2021)
Currently, conventional teaching materials and learning media have not met the learning demands in the 4.0 evolutionary era. It results in many students who do not understand the subject matter, so that the learning objectives have not been achieved optimally. This study aims to produce an inquiry-based interactive electronic module to support learning. This type of research is development research using the ADDIE model, which includes the analysis, design, development, implementation, and evaluation stages. The techniques used in collecting data are observation, interviews, and questionnaires. The instrument used to collect data is a questionnaire. The analysis used is qualitative descriptive analysis technique and quantitative descriptive analysis. The research results review subject matter experts who get very good qualifications (100%). The results of the learning design expert review are very good (90%). The results of the learning media expert review are good (86.7%). The individual test results are very good (97,3%). The small group test results are very good (95.7%). It can be concluded that the inquiry-based interactive e-module is very valid and feasible to use in learning. This research implies that teachers can use the developed media to help students learn.